Avaliação de propriedades psicométricas de um instrumento para análise da atuação de auxiliares em saúde bucal - Iara Souza Neves Braga (2021)
In Dentistry, Dental Surgery Assistants (DSA) are gaining more space by composing the oral health teams, favoring ergonomic and biosafety aspects, increasing productivity in the dental surgery and providing greater efficiency. In Brazil, in 2008, the Law 11,889 regulated the professional activity of this category. The regulation of the profession implies the adoption of procedures that allow to describe the professional profile and characterize the activities performed by these professionals. A questionnaire is an instrument that can be used for this purpose. The aim of this study was to measure psychometric properties of a questionnaire designed to identify the work characteristics of Dental Health Assistant (DHA). The project was approved by the Research Ethics Committee of the Federal University of Minas Gerais (CAAE n. 17378718.5.0000.5149 of 10/02/2019). The questionnaire was designed according to the Law 11,889 that regulated the professional activity of this profession, in Brazil. It contains 21 questions, seven referring to personal identification and 14 about professional attributions and was sent to 75 DHA through the WhatsApp app. The questionnaire was applied twice to the same participants, with an interval of one week. In the analysis of psychometric properties, internal consistency was verified through the total Cronbach's Alpha coefficient and temporal stability through Cohen's Kappa. The SPSS software version 25.0 was used for analysis. The internal consistency of the 14 questions related to the professional attributions resulted in a Cronbach's Alpha coefficient equal to 0.949 and a Cohen's Kappa coefficient greater than 0.6 in all questions. There was no major change in Cronbach's Alpha coefficient when any questions were removed. The psychometric properties found were considered satisfactory, revealing that it is an instrument with adequate reliability and temporal stability.